2014
DOI: 10.5539/jsd.v7n2p25
|View full text |Cite
|
Sign up to set email alerts
|

Rural Peoples’ Perception to Climate Variability/Change in Cross River State-Nigeria

Abstract: The rural people have been recognized as knowledge holders on climate variability/change and key actors for developing policies to mitigate and cope with its effects. The study attempts to assess perception level of rural people to Climate change in selected communities in Cross River State, Nigeria. Primary data were collected from 120 rural dwellers in 4 communities. This data centered on knowledge (awareness) level of climate variability/change causes, effects, mitigation and adaptive strategies. The data g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 7 publications
6
11
1
Order By: Relevance
“…Respondents stated in addition of the aforementioned, the appearance of diseases which is in agreement with the work of [24] which reported that strong winds and stormy weather were perceived by the communities and has led to occurrence of many diseases which affected both adults and children who are most vulnerable. Furthermore, the study of [25] in Bangladesh also revealed an unusual increment and unpredictability in the rainfall pattern.…”
Section: Discussionsupporting
confidence: 53%
“…Respondents stated in addition of the aforementioned, the appearance of diseases which is in agreement with the work of [24] which reported that strong winds and stormy weather were perceived by the communities and has led to occurrence of many diseases which affected both adults and children who are most vulnerable. Furthermore, the study of [25] in Bangladesh also revealed an unusual increment and unpredictability in the rainfall pattern.…”
Section: Discussionsupporting
confidence: 53%
“…It is pertinent to strengthen adaptation of poor farmers to increase their productivity. Ufuoku (2011) in Egbe at al (2014), corroborate this fact adaptation to climate change requires farmers to realize that the climate has changed and they must be assisted to identify useful adaptation strategies and implement them. This questions are what this study seeks to answer.…”
mentioning
confidence: 95%
“…Adaptation generally is primarily tailored towards agricultural productions principally through irrigation and planting crop resistant species, most local farmers are aware that the stress on their local environment and livelihoods has increased and low capacity for adaptation is a serious issue (Jones et al, 2011in Egbe, Yaro, Okon & Bisong, 2014. According to Pettengell (2010) in Egbe at al (2014), poverty, more than any other factor, determines vulnerability to climate change and limits adaptive capacity. It is pertinent to strengthen adaptation of poor farmers to increase their productivity.…”
mentioning
confidence: 99%
“…From the study, it was showed that crop yield is sensitive to variability in the time of onset and cessation of the rainy or growing season. Egbe et al (2014) studied the rural peoples' perception of climate variability in Cross River State, Nigeria. However, the study did not cover the effects of climate variability on livelihood of farmers, though it is a known that increasing poverty in rural areas has a link with climate variability.…”
Section: Introductionmentioning
confidence: 99%